2020
DOI: 10.1097/md.0000000000019518
|View full text |Cite
|
Sign up to set email alerts
|

Clinical case report

Abstract: Introduction: The incidence of Hashimoto's thyroiditis among patients who have Turner syndrome (TS) has increased, but Graves’ disease (GD) in patients with TS is rarely reported. Here we report a rare case of TS with GD accompanied by hypogonadotropic hypogonadism. Patient concerns: We report the case of a 16-year-old girl who complained nervousness, fatigue, marasmus, heat intolerance, sweating, palpitation, and tremor lasting for more than a month. She had no medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…It was previously reported that hyperthyroidism went into remission in a 17-year-old female with TS and GD after 18 months of treatment with MMI but recurred 9 months later, and thyroid function returned to normal after 2 years of retreatment with antithyroid drugs [ 22 ]. Similarly, another study showed that MMI was used successfully to control hyperthyroidism in a patient with TS and GD [ 23 ]. However, in another report, PTU failed to control hyperthyroidism in a patient with TS and GD and the patient had to undergo subtotal thyroidectomy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that hyperthyroidism went into remission in a 17-year-old female with TS and GD after 18 months of treatment with MMI but recurred 9 months later, and thyroid function returned to normal after 2 years of retreatment with antithyroid drugs [ 22 ]. Similarly, another study showed that MMI was used successfully to control hyperthyroidism in a patient with TS and GD [ 23 ]. However, in another report, PTU failed to control hyperthyroidism in a patient with TS and GD and the patient had to undergo subtotal thyroidectomy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports described the association between GD and TS [49,58,60,61]. As for HT, the prevalence rate of GD in TS girls is higher than in the general population (Table 2).…”
Section: Turner Syndromementioning
confidence: 99%
“…Patients diagnosed with Turner syndrome have a unique phenotype that includes a webbed neck, broad chest, and low posterior hairline. In addition, structural cardiac abnormalities, gonadal dysgenesis, hypertension and diabetes are some of the secondary sex characteristics observed in patients with Turner syndrome [ 2 , 3 ]. Nearly 40–60% of TS patients have a 45,X karyotype, on the other hand, 45,X/46, XX; 46,X,i(Xq); and other variants are observed in several TS patients [ 1 ].…”
Section: Introductionmentioning
confidence: 99%